Attitude Of Generation Z of The Batak Tribe In Preserving Ulos As A Cultural Heritage - Lamria Raya Fitriyani; Dewi Rachmawati (Ikatan Sarjana Komunikasi Indonesia, 2024)
Ulos is one of the cultural heritages of the Indonesian archipelago from the Batak Tribe. The use of Ulos varies from the Ulos giver to the recipient, so that the Ulos has a variety of motifs with different meanings, namely to suit the purpose of giving it. Through the attitudes and motivationÂ ofÂ Young generation regarding the preservation of Ulos, which has become the cultural identity of the Batak Tribe. This study aims to determine the Attitude of the young Generation of the Batak Tribe regtoarding Ulos in preserving it as a cultural heritage. The research was conducted using descriptive quantitative methods with young generation respondents from the Batak ethnic group in Jabodetabek. Several questions related to attitudes and motivation about Ulos were included in the questionnaire which became the instrument in this study. Theories and concepts used in this study are interests with indicators of encouragement from individuals, social motives, and emotional factors. In the attitude concept using indicators, cognitive, affective, konative, and also on internal factors and external factors in which there is group interaction. The results of the study show that young generation has a positive attitude and motivation in preserving Ulos as a cultural heritage. The cognitive level of the younger generation of the Batak tribe is relatively low, so it needs to be improved, namely gaining understanding and knowledge to study ulos cloth so that it can continue to preserve it. This of course requires the role and support of parents and family.